Cephalopod assemblages and depositional sequences from the upper Cenomanian and lower Turonian of the Iberian Peninsula (Spain and Portugal) - Barroso-Barcenilla, F.; Callapez, P.M.; Ferreira Soares, A.; Segura, M. (Journal of Iberian Geology, 2011)
The comparison and correlation of the biostratigraphic successions identified in the upper Cenomanian and lower Turonian of the Iberian Trough (IT, Spain) and the Western Portuguese Carbonate Platform (WPCP, Portugal) allows differentiating nine cephalopod assemblages (1 to 9), with notably different taxa, and two (3rd order) depositional sequences (A and B). Some of these main intervals can be divided in minor ones, such as assemblage 4 (in 41 and 42) and sequence B (in B1 and B2). Assemblages 1 to 3 are related with sequence A, and assemblage 4 to 9 with sequence B (specifically, 4 to 6 with B1, and 7 to 9 with B2). The analysis and interpretation of these biostratigraphic data allows us to infer certain palaeoecologic turnovers that happened in the studied basins, both with external origin or due to local tectonic and palaeogeographical changes. Though partially altered by hypoxic phenomena (especially the sequence B1, assemblage 4) and local tectonics (mainly in the WPCP), in each of these cycles there were events of extinction of the cephalopods from shallow environments and survival of those from pelagic or deep environments, of settling of new environments, and of adaptation to them caused, successively, by intervals of low, ascending and high sea-level.